Avaliação da influência de fibras de polipropileno na resistência efetiva de um solo argiloso - Rocha, Sabrina Andrade (2019)
The use of soil-fiber has been recognized as a viable technique of soil improvement in numerous geotechnical applications. However, existing research has not yet established the fundamental mechanisms controlling the behavior of clay-fiber mixtures and the constraints that may affect their performance. On the other hand, there is a growing increase in the development of methodologies for predicting soil-fiber behavior, as well as the use of constitutive models for mixtures based on individual properties soil and fibers. However, few studies have evaluated the effectiveness of the methods available and the peculiarities that may affect the results. In this context, the present work aims to contribute to the understanding of the shear strength and deformability behavior of a clayey soil with the inclusion of short fibers from recycled polypropylene, through unconfined uniaxial compression tests, direct shear strength and triaxial compression (drained and undrained) tests. In addition, the research evaluated the effectiveness of some soil-fiber shear strength prediction methods. This research evidenced that, in all tests, the fibers improved the shear strength of the clayey soil, increasing its ductility and initial stiffness. It was also verified that the interaction mechanisms between the soil and the fibers, and consequently the shear strength of the composite, were not influenced by the drainage condition or by the development of pore water pressures during shearing, since values of effective shear strength at failure in drained condition and undrained condition were similar. Regarding the shear strength prediction methods, both in terms of total and effective stresses, analyses presented few discrepancies in relation to the results obtained experimentally, but it is verified that the soil-fiber interaction coefficients strongly influence the results of predictability and must be analyzed in a more effective way to reduce the discrepancies capitalized in this research.